Gandhi on Women Emancipation (International Journal of Innovative Research in Engineering & Management, 2021)
The present century, the age of humanism is the high time to  provide an equal privilege and dignity to all the suppressed  and oppressed sections of the society. Therefore, Women  emancipation and upliftment has been becoming a burning  issue day by day in the present century. Unlike many noble  souls who focused on this issue, Gandhi is one of them.  Gandhi had distinct views regarding different issues related to  women. In this article we shall try to analyse Gandhi’s views  regarding different women issues in the present society.  Gandhi focused on different women issues like marriage,  divorce, widow remarriage, pardah system, dowry system,  women education, political involvement of women etc. So we  shall try to find the way out that Gandhi prescribed regarding  different women issues existing in the society.
Keywords: Women; Emancipation; Political Involvement; Widow